Cross‐cultural translation and validation of the Malay version of the Swanson, Nolan, and Pelham Parent Rating Scale of attention deficit hyperactivity disorders symptoms among Malaysian probands: A preliminary study - Jusoh, Masnira; Dzulkarnain, Ahmad Aidil Arafat; Rahmat, Sarah; Musa, Ramli; Che Azemin, Mohd Zulfaezal (John Wiley & Sons Australia, Ltd, 2020)
The aim of this study is to evaluate the psychometric properties of the Malay version of the Swanson, Nolan, and Pelham Parent Rating Scale of attention deficit hyperactivity disorders (ADHD) symptoms (M-SNAP-IV). For this purpose, the SNAP-IV scale was translated into the Malay language and was pilot-tested on 91 parents of children aged 8 to 11 years (ADHD [n = 36] and non-ADHD children [n = 55]). The findings depicted that the M-SNAP-IV has excellent content validity, internal consistency, and test-retest reliability. The M-SNAP-IV is a valid and reliable screening tool to detect ADHD symptoms in children and has the advantages to assess the specific presentation of ADHD.